A Yamazaki-type estimate to a space-time fractional diffusion equation - Lima, Maria Elismara de Sousa; Oliveira, Edmundo Capelas de; Viana, Arlúcio da Cruz (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
In this work, we develop the Yamazaki inequality and estimates of the Mittag-Leffler family associated with the space-time fractional diffusion equation in 𝐿𝑝-weak spaces. This result generalizes the inequality given by Yamazaki (2000) for the heat semigroup, which was generalized by Ferreira and VillamizarRoa (2006) for heat semigroup associated with the fractional Laplacian, and Caicedo et al (2021) for the Mittag-Leffler family associated with the time-fractional diffusion equation.